P184 A cost-saving pathway for diagnosing patients with suspected obstructive sleep apnoea (OSA) in the community. (12th November 2019) - Devani, N; Aslan, T; Morgan, S; Mandal, S
Abstract : Background: OSA is a major healthcare challenge with current UK data estimating that up to 85% of individuals with OSA are undiagnosed. Promoting awareness and improving access to diagnostics is fundamental in addressing these missing cases. Diagnosis usually occurs in secondary care with data from our trust in 2017 revealing long wait times to undertake a sleep study and an average 2 clinic attendances before a diagnosis made. This places a considerable time and emotional burden on the patient and a financial and logistical burden on the hospital. Method: To address these long wait-times, streamline the patient pathway and improve access to diagnostics, we piloted a monthly community outreach OSA clinic run from within a local General Practice (GP). The clinic received referrals directly from other neighbourhood GPs and issued patients with a portable diagnostic device to allow them to undertake a home sleep study. The clinic was supported by a 'virtual MDT' run by the hospital team where the results were reviewed and outcomes communicated directly to both patients and GPs. Pathway costs, waiting times and patient related experience measures were calculated and compared to the conventional hospital-based diagnostic pathway. Results: The pilot ran from Jan 2018 to Feb 2019. 78 patients were referred and investigated along the outreach pathway with an average estimated cost per patient of £439.72 compared to £831.77 for the hospital-based diagnostic pathway. Table 1 provides a detailed cost breakdown and assumes the community clinic will be run by a band 6 health-care professional. When compared to the hospital pathway, data demonstrated a significant improvement in patient waiting referral to diagnosis made (37 days vs 239 days) and commence treatment (128 days vs 267 days) (all p<0.0001). Measures of patient satisfaction were significantly higher within the outreach clinic group compared to the hospital-based diagnostic group. Conclusion: A hospital led community-based pathway can achieve cost-savings whilst resulting in more timely diagnosis of OSA within a local setting thereby widening access to diagnostics. It is favoured by patients and aligns with the NHS long-term plan.